The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/brs.0b013e3182518859
|View full text |Cite
|
Sign up to set email alerts
|

Osteoconductive Bone Graft Extenders in Posterolateral Thoracolumbar Spinal Fusion

Abstract: Osteoconductive BGEs combined with local spine autograft and/or bone marrow aspirate have comparable fusion rates, similar functional outcomes, lower complication rates, and a lower risk of donor site pain than ICBG. Caution should be taken in interpreting these findings, given the low quality of the studies and the heterogeneity in the results. Randomized controlled studies using blinded assessments are required to help elucidate more conclusive evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…In comparison to previous studies, which show either an inferiority of calcium phosphates compared to autograft or equivalence evidenced through weaker endpoints, we demonstrate equivalent performance of AG, BCP granules and BCP putty by an array of strong assessment methods. In clinical literature, we can find conflicting evidence about the efficacy of calcium phosphate materials as bone graft materials for spine fusion . Physicochemical properties of biomaterials are rarely discussed in clinical literature and it is often overlooked that these properties strongly influence the performance of calcium phosphate bone graft materials.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to previous studies, which show either an inferiority of calcium phosphates compared to autograft or equivalence evidenced through weaker endpoints, we demonstrate equivalent performance of AG, BCP granules and BCP putty by an array of strong assessment methods. In clinical literature, we can find conflicting evidence about the efficacy of calcium phosphate materials as bone graft materials for spine fusion . Physicochemical properties of biomaterials are rarely discussed in clinical literature and it is often overlooked that these properties strongly influence the performance of calcium phosphate bone graft materials.…”
Section: Discussionmentioning
confidence: 99%
“…Fusion rates above 85% at 2 to 3 years post-procedure have been demonstrated for both local and iliac crest bone grafts [12,32]. Synthetic BGEs have been associated with similar rates of fusion success, with one recent systematic review [7] reporting an 86.4% fusion rate when ceramic materials were utilized as the BGE, while another systematic review [13] found pooled fusion rates ranged from 75% with calcium sulphate to 98.2% with a combination of hydroxyapatite and tricalcium phosphate. The current study included supplemental posterolateral fusion for which greater quantities of bone graft are required.…”
Section: Discussionmentioning
confidence: 99%
“…While these products provide a suitable scaffolding upon which to build new bone, they are inherently unable to stimulate bone growth without the patient's own bone or marrow to augment the process. Alternate options such as tricalcium phosphate, calcium sulfate and hydroxyapatite, while possessing osteoconductive properties, are associated with equivocal results regarding fusion rates [13]. To address the shortcomings of the currently available technology, a fully-resorbable hybrid biosynthetic autograft extender for use in spinal fusion was developed (InQu ® , ISTO Technologies, Inc., St. Louis, MO).…”
Section: Introductionmentioning
confidence: 99%
“…Autogenous iliac crest bone graft has long been considered the “gold standard” used in spinal fusion procedures because its characteristics, such as osteogenesis, osteoinduction, and osteoconduction, are ideal for promoting fusion from a biological perspective [3]. But a series of complications accompanied by autogeneous bone grafting are inevitable.…”
Section: Introductionmentioning
confidence: 99%